Blackhole Detection and Prevention Strategies in DTN (International Journal of Engineering and Computer Science, 2016)
Delay Tolerance Network (DTN) is a network which is used for sparse networks where network connectivity is not possible between two nodes so for this number of intermediate nodes is used to transfer messages. These intermediate nodes may cause network so security in DTN is a very difficult task. In this paper blackhole attack and its various detection techniques are presented with literature review of different research papers that covers black hole detection and prevention mechanism. A blackhole node behaves maliciously in network and provides wrong data routing information or may drop the messages receives from other nodes. So it is difficult to find black hole attack and prevent network from them. These techniques are used in the prevention of network from blackhole attack.